(X-4)(x-5)=(x-4)(2x+3)=0

Simple and best practice solution for (X-4)(x-5)=(x-4)(2x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-4)(x-5)=(x-4)(2x+3)=0 equation:



(X-4)(X-5)=(X-4)(2X+3)=0
We move all terms to the left:
(X-4)(X-5)-((X-4)(2X+3))=0
We multiply parentheses ..
(+X^2-5X-4X+20)-((X-4)(2X+3))=0
We calculate terms in parentheses: -((X-4)(2X+3)), so:
(X-4)(2X+3)
We multiply parentheses ..
(+2X^2+3X-8X-12)
We get rid of parentheses
2X^2+3X-8X-12
We add all the numbers together, and all the variables
2X^2-5X-12
Back to the equation:
-(2X^2-5X-12)
We get rid of parentheses
X^2-2X^2-5X-4X+5X+20+12=0
We add all the numbers together, and all the variables
-1X^2-4X+32=0
a = -1; b = -4; c = +32;
Δ = b2-4ac
Δ = -42-4·(-1)·32
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{144}=12$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-12}{2*-1}=\frac{-8}{-2} =+4 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+12}{2*-1}=\frac{16}{-2} =-8 $

See similar equations:

| z+135=450 | | X+18=36x | | (7x+15)+(x+13)=180 | | 12x-20=220 | | 6x+10+7x=180 | | 6x=9/2x+15 | | -3(2x-6)=-18 | | 100=X+24x | | 7x-3+5x=-3 | | x-11=4x+26 | | 2x=x+4= | | (1x+9)+(2x+6)=180 | | 3(2r-5)=27,2r5 | | |8y+4|=2|y−1||8y+4|=2|y−1| | | 10x+40/6=50 | | 5g=-55 | | 5n+-2n=-3n | | X-30=100x | | 35+x=52.50 | | 4(3x-2)-5x+x=0 | | 5x/3-1=24 | | 4-5x-x=16 | | 7/3=4/h | | 2x+6=1x+9=180 | | 7=-0.8y+27 | | w^2+16w+260=0 | | 4.5=2*3.14r | | 8x-10=A | | 3(2r-5)=272r-5 | | 7(d=5)=91 | | -8(2y+3)-12=19y-6y+4 | | 2x+1-3x=7+4-6x |

Equations solver categories